Characterization of Virulence Factors in Multidrug-Resistant Escherichia Coli Isolated from Intestinal and Extra - Intestinal Clinical Samples - Baral, Soma Kanta; Dangol, Geeta; Manandhar, Krishna Das; Poudel, Pramod (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Introduction: The global issue of antimicrobial resistance to human health is becoming increasingly concerning. Escherichia coli (E. coli) is a widespread pathogen that causes a wide range of illnesses. This is because multidrug-resistant (MDR) E. coli bacteria have emerged, proliferated, and remained persistent. Antimicrobial resistance is more predominant among pathogenic organisms compared to the commensal ones. The correlation between resistance and virulence factors could be a result of the successive exposure of pathogenic organisms to antibiotics. Therefore, the goal of our study was to detect some virulence factors in multidrug-resistant E. coli that were isolated from fecal and other clinical samples. Methods: A laboratory-based cross-sectional study was conducted from October 2023 to March 2024, a period of six months. E. coli was isolated using standard microbiological methods from a range of clinical samples. Antibiotic susceptibility was done to identify MDR E. coli by Kirby-Bauer disk diffusion method. Different phenotypic assays were used to detect virulence factors. Results: Out of 318 isolated E. coli from different clinical samples, 160 (50.3%) were found to be multidrug-resistant. Higher distribution of MDR E. coli (51.9%) was found in extra-intestinal samples than fecal specimen. MDR E. coli strains were highly resistant to most antimicrobials. The most common virulence factor was cell surface hydrophobicity (100%) followed by motility (83.7%), biofilm production (36.2%), serum resistance (25%),hemolysin production (15%) and gelatinase production (2.5%). There were multiple virulence factors found in 156 (97.5%) MDR E. coli isolates. Conclusion: It was discovered that MDR E. coli strains obtained from patient intestinal and extra-intestinal samples were more virulent and more resistant to drugs.